EFISIENSI PRODUKSI BAWANG MERAH DI KABUPATEN BREBES - , MAYA KARTIKA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine (1) amount of income earned by red onion farmer in Brebes District, (2) factors that influence the red onion production in Brebes District, (3) level of technical efficiency, price efficiency and economic efficiency of red onion farm in Brebes District, and (4) factors that affect the farmersâ income. The study used several analysis method e.g., analysis of income, Stochastic Frontier production function analysis and multiple regression analysis by using OLS (Ordinary Least Square). It used primary data which obtained from interviews with the onion farmers from Brebes district. This study resulted that farmersâ income in dry season is greater than rainy season. Factors that affect significantly and have positive value on onion farm production during the dry season are land area, number of seeds and insecticides while the factors affecting red onion production during rainy season are land area, number of seeds, organic fertilizer, KCl fertilizer and labor. Based on the calculation of the technical efficiency, it obtained average technical efficiency during dry season by 99,01 percent while in rainy season 99,22 percent